Measuring tax complexity across countries: A survey study on MNCs - Thomas Hoppe; Deborah Schanz; Susann Sturm; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2019)
Despite prior literature emphasizing the increasing role of tax complexity, there is still no comprehensive tax complexity measure. This paper fills this gap and introduces the Tax Complexity Index (TCI), which consists of a tax code subindex and a tax framework subindex. The indices are designed to capture the multidimensional nature of tax complexity from an MNC's perspective and extend previous measures that have so far only focused on selected countries or facets of tax complexity. Based on a survey of highly experienced tax consultants of the largest international tax services networks, the indices are calculated for 100 countries for the year 2016. Our findings indicate that the level of tax complexity varies considerably across countries. From a global perspective, tax complexity is strongly affected by the complexity of transfer pricing regulations in the tax code and by the complexity of tax audits in the tax framework. While we identify countries that turn out to be complex in both their tax code and tax framework, we also observe that many countries differ in their rankings on tax code and tax framework complexity, i.e., they either have a high tax code complexity and a low tax framework complexity or vice versa. When analyzing the associations between tax complexity and other country characteristics, we identify different correlation patterns. For example, we find that tax (framework) complexity is negatively associated with countries' governance, suggesting that strongly governed countries tend to have less complex tax frameworks. In contrast, we find a positive association between tax (code) complexity and the statutory tax rate, indicating that high-tax countries tend to have more complex tax codes. However, none of the observed associations is very strong. We conclude that tax complexity represents a distinct country characteristic and propose to use the TCI and its subindices as new proxies for MNCs' varying exposures to tax complexity in the assessment of country-specific corporate decisions.
Keywords: H20; H25; C83; O57; 330; tax complexity; tax index; tax system; multinational corporations; tax consultants